NATIONAL SECURITY: A RE-ENGAGEMENT WITH CONCEPTS, STRUCTURES, AND PLANS - Ochoga Edwin Ochoga; Binta Sidi (International Studies Journal)
The paper  has demonstrated how Nigeria national security strategy was militarily in the past and how the amended  Nigeria national security strategy under the President Buhari’s administration brought human security to it which is  in line with global best practices.   Legally, the Nigerian constitution puts security in the Exclusive List which gives the Federal Government the exclusive jurisdiction to legislate on national security matters. The sub-national governments do not have the legal-rational authority to decide on security matters, as the federal government controls the national security architecture. Even with the emergence of the series of violent non-state actors which is threatening Nigeria’s national security, the federal government still has the monopoly of power over national security. Although this is a constitutional matter, it is a concern against the effective implementation of the National Security Strategy.